2018
DOI: 10.1186/s40163-018-0093-5
|View full text |Cite
|
Sign up to set email alerts
|

To the moon: defining and detecting cryptocurrency pump-and-dumps

Abstract: Pump-and-dump schemes are fraudulent price manipulations through the spread of misinformation and have been around in economic settings since at least the 1700s. With new technologies around cryptocurrency trading, the problem has intensified to a shorter time scale and broader scope. The scientific literature on cryptocurrency pumpand-dump schemes is scarce, and government regulation has not yet caught up, leaving cryptocurrencies particularly vulnerable to this type of market manipulation. This paper examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(80 citation statements)
references
References 11 publications
3
68
0
Order By: Relevance
“…On the other hand, our results may be seen as fuel for a broader discussion about the role of cryptocurrencies. While clearly potentially helpful for citizens of countries beset by hyperinflation, evidence on the strong connection to illicit activity and the, as of yet, unrealized promise of providing a means to increase financial inclusion would seem to weigh in with arguments that the cryptocurrency's growth is to be seen as cause for concern-e.g., in the light of price manipulation (Griffin and Shams 2019), heavy electricity use associated with Bitcoin mining (Krause and Tolaymat 2018) and the increased occurrence of cybercrimes and frauds involving cryptocurrencies (Corbet et al 2019;Kamps and Kleinberg 2018;Li et al 2018;Su 2019).…”
Section: Implications For Scholars Of Digital Currencymentioning
confidence: 99%
“…On the other hand, our results may be seen as fuel for a broader discussion about the role of cryptocurrencies. While clearly potentially helpful for citizens of countries beset by hyperinflation, evidence on the strong connection to illicit activity and the, as of yet, unrealized promise of providing a means to increase financial inclusion would seem to weigh in with arguments that the cryptocurrency's growth is to be seen as cause for concern-e.g., in the light of price manipulation (Griffin and Shams 2019), heavy electricity use associated with Bitcoin mining (Krause and Tolaymat 2018) and the increased occurrence of cybercrimes and frauds involving cryptocurrencies (Corbet et al 2019;Kamps and Kleinberg 2018;Li et al 2018;Su 2019).…”
Section: Implications For Scholars Of Digital Currencymentioning
confidence: 99%
“…Several works addressed the cryptocurrency topic with a focus on manipulation patterns. In [22], authors provided a first look of cryptocurrency pumpand-dump schemes and found that such frauds target specific cryptocurrency coins and exchanges. However, their work was preliminary and did not yet analyze the coordination of pump-and-dumps in online chat groups, nor the means by which misinformation about specific coins is spread on, like on social media.…”
Section: A Cryptocurrency Manipulationsmentioning
confidence: 99%
“…Reuters. Available at: https://www.reuters.com/ article/us-amazon-com-jobs-automation-insight/amazon-scraps-secret-ai-recruiting-tool-that-showed-bias-againstwomen-idUSKCN1MK08G (accessed 19.11.2020 [Caldwell, Andrews, Tanay, 2020;Kamps, Kleinberg, 2018;Van Der Wagen, Pieters, 2015;Wilner, 2018].…”
Section: современныеmentioning
confidence: 99%